Digitalization of bank and finance in Africa - (:unkn) unknown (My University, 2024)
This doctoral thesis examines the effects of digitalization on economic development in Africa. It contributes to the empirical analysis of the effects of digital technologies adoption on financial inclusion and economic development. In Chapter 2, we investigate the impacts of the digitalization of financial services on financial inclusion in Africa. The results indicate that mobile money and digital payments have a positive and significant impact on banking rates, access to credit, and savings mobilization. Chapter 3 is an extension of the first chapter on financial inclusion. We empirically analyze the effects of ICT usage on business credit access in Sub-Saharan Africa (SSA). On one hand, the results show that mobile phone subscription, fixed broadband subscription, and individual internet usage have positive effects on credit granted to the private sector. On the other hand, the results also reveal that mobile phone subscription, internet access, and internet usage are associated with the increase in bank loans in Africa. Chapter 4 explores the empirical impact of ICT adoption on trade between SSA countries from 2000 to 2018. The results suggest that ICT usage, especially Internet usage, has positive and significant effects on exports and negative effects on imports of primary products and the total of goods. Within the framework of the free trade agreement adopted by the African Union, this chapter demonstrates the role of digital tools in the success of this important instrument. Finally, in Chapter 5, we assess theimpact of mobile money adoption on inflation and economic growth in Africa through a Difference-in-Differences (DiD) model. The results show that mobile money facilitates money circulation, thereby stimulating economic activity without causing an uncontrolled increase in inflation. They also reveal that the adoption of mobile money contributes to the economic growth of countries that have adopted it.
Keywords: African Research